The Applying Islamic Financial Accounting Standards and Its role in Raising The Creditworthiness of Islamic Financial Institutions " A field Study on A sample of Sudanese Banks" - Alshami, Sondous Abdalaziz; Mohammed, Abdelrahim Mahgoub Ahmed; Salama, Maha Mosa Mohammad; Sanad, Yasir Tajelssir Mohammed; Somij, Elhadi Mekki Mawan (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to study and know the impact of applying banking governance mechanisms on increasing the creditworthiness of Sudanese banks, studying and knowing the impact of adherence to the principles of banking governance on increasing the creditworthiness of Sudanese banks. Is there a statistically significant relationship between adherence to the principles of banking governance and the increase in the creditworthiness of Sudanese banks? The study used the descriptive analytical method, To achieve the objectives of the study, the following two hypotheses were tested: There is a statistically significant relationship between banking governance mechanisms and the increase in the creditworthiness of Sudanese banks, there is a statistically significant relationship between commitment to the principles of banking governance and an increase in the creditworthiness of Sudanese banks, The study reached many results that proved the validity of the two hypotheses, including: that the application of banking governance helps to increase the creditworthiness of Sudanese banks. The study recommended the necessity of activating the basic components that characterize corporate governance in banks to detect weaknesses in each component and achieve benefit in dealing with them preventively and remedially.
Keywords: banking governance; governance mechanisms; Creditworthiness